This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A nice anti-solution.
You have to depend on the trial by this method ... We should rather try to reject one answer before itself.. It would be more mathematical and logical...
The question can be expressed as
2
x
+
9
=
1
3
−
x
⟹
(
2
x
+
9
)
=
(
1
3
−
x
)
2
⟹
(
2
x
+
9
)
=
x
2
−
2
6
x
+
1
6
9
⟹
x
2
−
2
8
x
+
1
6
0
=
0
⟹
x
2
−
2
0
x
−
8
x
+
1
6
0
=
0
⟹
x
(
x
−
2
0
)
−
8
(
x
−
2
0
)
=
0
⟹
(
x
−
2
0
)
(
x
−
8
)
=
0
⟹
x
−
2
0
=
0
(or)
x
−
8
=
0
⟹
x
=
2
0
(or)
x
=
8
But, if we substitute x = 2 0 in the question, the equation does not satisfy, so x is not equal to 2 0 .
So, x = 8
First thing to note is that 2x+9 is under root, so it can't be negative. So 2x+9>0. So x>-9/2.And Root 2x+9 Is positive so it should be less than 13. Squaring both sides and then solving the equation we find the value of x to be 8 or 20. But x can't be greater than 13. So the value of x is 8.
You have found that x> -9/2. From this x can be positive or negative. If x would be negative, then you can't say that x would be less than 13. If x would be positive then only you can say it would be less than 13.
Problem Loading...
Note Loading...
Set Loading...
I (taking the easy way out) tested 8 and 20 in the equation rather than solving it algebraically. 8 workes and 20 did not, so the answer is 8.